Senescence processes in plants - Gan, Susheng (Blackwell, 2012)
The scientific and economic significance of plant senescence means that much effort has been made to understand the processes involved and to devise means of manipulating them agriculturally. During the past few years there has been considerable progress in this regard, especially in the molecular, genetic and genomic aspects.